What is Scots? - Lemeshchenko-Lagoda, Viktoriia; Лемещенко-Лагода, Вікторія Володимирівна; Лемещенко-Лагода, Виктория Владимировна (My University, 2019)
Many people have heard about the Scots language but aren't sure what it is. Scots has been spoken in Scotland for many centuries and is found today throughout the Lowlands and Northern Isles. It is mainly a spoken language with a number of local varieties, with its own distinctive character each
Keywords: the scots; scottish language; Scotland; history of scotland